Factors affecting occupational stress among teachers of a secondary school in Sarawak - Yong, Ing Thung (1999)
This study aimed to examine factors affecting occupational stress among teachers of a secondary school in Sarawak. The specific objectives of this study are to examine the significant difference between occupational stress levels of different subgroups according to their (1) gender, (2) marital status, (3) service grade, (4) length of years of teaching experience, (5) race, (6) age group, and (7) education level. This study also examined the significant difference between social support of different subgroup of teachers according to gender and marital status. The research designs used by this ex post facto study are independent two-tailed t-test and One Way ANOVA. The respondents compound of95 teachers who are selected by using the stratified random sampling. Teacher Stress Inventory (TSI) was used to determine the factors that cause occupation stress. Teacher Stress Level Inventory (TSLI) was used to determine the level of stress among teachers. The Social Support Behaviour (SS-B) scale was used to determine the support from family and friends. The results reveal that the occupational stress levels of teachers is generally low. The factors that they perceived to be most stressful is pupil misbehavior whereas the two least important factors are time pressure and poor working conditions. The results indicated that there is a significant difference in stress according race. Chinese teachers are found to be facing most stress and compared to Sarawak native teachers and Malay teachers. It is also found that there are significant difference in friend social support by gender and marital status. Finally, the results reveal that there are moderate or substantial correlation between four stress factors (pupil misbehavior, poor working conditions, time pressure and poor school ethos) with teacher stress levels.